EPCO-21. CORE REGULATORY CIRCUIT TRANSCRIPTION FACTORS DRIVE EXPRESSION FROM HIGH LEVEL AMPLICONS IN PEDIATRIC HIGH-GRADE GLIOMAS. (12th November 2021) - Deng, Davy; Dubois, Frank; Crane, Alexander; Harutyunyan, Ashot; Beroukhim, Rameen; Bandopadhayay, Pratiti
Abstract: BACKGROUND: Pediatric High-Grade Gliomas (pHGGs) show recurrent high-level amplifications around the oncogenes MET, MYCN and EGFR. However what drives expression of the oncogenes from these amplicons remains unclear. We aim to discover enhancers on these amplicons that are responsible for oncogene expressions and the core regulatory transcription factors (TFs) they bind. METHOD: Using RNA-seq from 12 pHGG cell lines, we identified groups of high and low-expressing pHGG lines for MET, MYCN and EGFR. We then compared the H3K27Ac ChIP-seq between the two groups using diffbind. This allowed us to identify statistically significant peaks that are differentially activated in the oncogene-high v.s. oncogene-low expressing groups. Additionally, we overlapped the positions of these candidate oncogene enhancers with the regions that are recurrently incorporated into high-level amplicons based on published whole genome sequencing data. Using a previously defined set of core regulatory TFs we determined which TF binds the amplified oncogene enhancers and could be driving oncogenic expressions of MET, MYCN and EGFR in pHGGs. RESULTS: We identify 3 cell lines for both the high- and low-expressing groups for each oncogene. Cell lines with high expression of the oncogene showed distinct enhancers with significant enrichment in H3K27Ac compared to the cell lines with low expression for each oncogene. Of all enhancers with enrichment high oncogene expression groups those with binding sites for known pHGG core regulatory circuit TF were preferentially incorporated into the high-level amplicons of the oncogene. We also identified core TFs that bind enhancers for MYCN, EGFR and MET as well as core TFs that are unique to a single oncogene. CONCLUSION: We identified candidate core transcription factor that drives expression of multiple oncogenes in pHGG. These could serve as a potential novel therapeutic target for pHGGs with addiction to MYCN or RTK signaling.